A prospective study: Investigating the use of oncologist-read CT scans in the investigation of suspected malignant spinal cord compression - Fairhead, Sarah (Division of Radiology, 2018)
Background: Spinal cord compression is a common complication of advanced cancer with significant consequences for individual patients and health care systems as a whole. This condition requires a radiologist reported MRI scan to diagnose, which is a limited resource in many settings. There are no data comparing MRI with multi-detector CT scan, a more accessible resource, for the diagnosis of this condition. Objectives: To investigate whether CT scans assessed by radiation oncologists should be used to diagnose and manage spinal cord compression in patients with advanced cancer by assessing its overall accuracy, including sensitivity and specificity, as a diagnostic test. To collect preliminary data to assist in ethically sound decision making regarding the rational allocation of MRI scans, which are known to be a scarce medical resource. Methods: Eight radiation oncologists (RO's) were given case histories and CT scan images for twenty cancer patients who had presented with possible spinal cord compression (SCC). They were asked to answer questions aimed to assess whether CT scan can be used to diagnose and guide treatment for spinal cord compression and how accurate an investigation CT scan is in this setting compared to the gold standard, MRI. Results: In 84% of assessments, RO's were able to correctly identify the absence or presence of SCC using CT scan. In 38% of assessments, RO's were able to correctly identify the level of SCC and would have treated that level exclusively. In 69% of assessments, the correct level would have been treated with or without additional non-compressed levels. The overall accuracy of CT scan to detect the absence or presence of SCC was 84%. The overall sensitivity was 83%. The overall specificity was 85%. Individual RO's scored an average of 83% (range 62-100%) for questions testing their ability to diagnose the absence or presence of SCC using a CT scan. Individual RO's scored an average of 69% (range 38-89%) for questions testing their ability to treat the level of compression and an average of 38% (range 13-56%) for questions testing their ability to treat the level exclusively. In 40% of assessments RO's reported that they would feel confident treating with only a CT scan. Individual RO confidence levels ranged from 0-66%. In 51% of assessments, the RO's would have changed their treatment plans if an MRI reported by a radiologist was available. Conclusion: Spinal CT scans reported by radiation oncologists are reasonably sensitive and specific for the detection of spinal cord compression. However, this imaging modality should not be used, in centers where radiology reported MRI is available, to diagnose and treat spinal cord compression, due to the relative inaccuracy of this test in determining the appropriate treatment for this condition.